(untitled) (Journal of the College of Basic Education, 2022)
The bricks product from Al-Azezia factories suffer from many problems in forefront of them decrease in strength and density, in addition to increase in brittleness, salts, and absorption. Factory Arth AL-Karat chosen as a sample for this study. We chose two routes of work; the first route concluded the work with the materials of bricks site (clays) without any processing about dispersion of clays, sieving, and addition different percentage weight of silica type Erthema (0%, 5%, 10%, 15%, 20%, 25%), followed by mixing and forming in semi dry. After that drying and heat treatment at a temperature 1150oC for 2hrs. This process is the same as nearly in Factory Arth AL-Karat except without addition of silica and determined heat treatment temperature. The second route concluded washing the clays by water from Al-Azezia water station for three days, after that drying and making the same steps in first route. The measurement conducted with percentage of salts in water (TDS) for Arth AL-Karat factory site, the value is too much about 2000ppm, but for Al-Azezia water station about 500ppm. As well as measurement density, water absorption, porosity, pressure strength, splitting strength, hardness, and the proportion of salts on the surface of samples. The results show a significant improver in samples with second route